(untitled) (Sains Humanika, 2019)
The hybrid method of video and 360Â° image in silat learning is the solution of video based learning issues on the minimum of interactive activities, lack of interaction between user and video and limited point of view. The aim of this research is to identify the effectiveness of silat learning courseware using the hybrid method of video and 360Â° image towards students’ achievement in silat subject. This research is also done to identify the usability of silat learning courseware based on easy to learn, interface and satisfaction matrixes. Pre-test and post-test were conducted to measure students’ achievement while usability questionnaire was used to measure the usability of silat learning courseware using the hybrid method of video and 360Â° image. The research found that silat learning courseware using the hybrid method of video and 360Â° image gave positive impact towards students’ achievement in silat subject. The level of usability of the silat learning courseware is high with the mean score for all the matrixes is over 4.00. This research shows that the usage of multimedia courseware especially using the hybrid method of video and 360Â° image is useful for students, help them to increase their achievement in silat and encourage the usage of multimedia based learning in silat learning in Malaysia.